'The Common Camp': temporary settlements as a spatio-political instrument in Israel-Palestine. Issue 1 (2nd January 2017) - Katz, Irit
Abstract : From their emergence in the 19th century to their current global proliferation, camps have been created extensively by and for different populations under the modern state order. Whether employed by national and colonial powers as instruments of control, or constructed ad hoc by displaced populations as makeshift spaces of refuge, camps are used as a versatile instrument for the rearrangement of people in space. In Israel-Palestine, camps are part of the significant geopolitical changes related to the state-building project and to the mass displacement it caused, providing a core example of similar enterprises of territorial alternation and social engineering. While the Palestinian refugee camps are well recognised and studied, many other types of camps which have appeared in the region over the last century together form a distinctive spatial paradigm. Through its particular manifestations in Israel-Palestine, this article examines the camp as a central instrument by which modern societies and territories are administered, negotiated and reorganised. The identification, understanding and re-definition of the camp's multifaceted spatial vocabulary allows to better understand this encompassing phenomenon which becomes increasingly relevant and urgent in today's migration age.